A study of student teachers' role perception before and after student teaching - Marquez, Julieta Fronda ([Bloomington, Indiana] [s.n.], 1964)
The main purpose of this exploratory study was to analyze the role perception of student teachers before and after their student teaching period. A survey of literature was first made to construct the Teacher Role Check List. This instrument was in the form of paired comparisons and yielded scores representing the relative importance of the different role groups and roles according to the respondents. Additional data were obtained from the folders of the student teachers in the School of Education Records Office. There was only a slight change in the way student teachers perceive the roles of teachers after student teaching but this change is geared toward the role perception of supervising teachers. Methods course intructors and personal factors do not have significant influence in the role perception of student teachers.
Bibliography: leaves 125-129.
Dissertation (D.Ed.)--Indiana University.
Keywords: Student teaching